2021
DOI: 10.3389/fcimb.2021.696719
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Trypanosoma cruzi Strains Is Related to the Differential Expression of Innate Immune Receptors in the Heart

Abstract: Resistance or susceptibility to T. cruzi infection is dependent on the host immunological profile. Innate immune receptors, such as Toll-like receptors (TLRs/TLR2, TLR4, TLR7, and TLR9) and Nod-like receptors (NLRs/NOD1 and NLRP3 inflammasome) are involved with the resistance against acute experimental T. cruzi infection. Here, we evaluated the impact of T. cruzi virulence on the expression of innate immune receptors and its products in mice. For that, we used six T. cruzi strains/isolates that showed low (AM6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…T. cruzi molecules such as surface glycoinositolphospholipids (GPIs) and parasite DNA/RNA sequences can be sensed by TLRs ( Macaluso et al, 2023 ). In fact, several investigators have shown the significance and involvement of TLRs in the control of T. cruzi infection ( Caetano et al, 2011 ; Castillo et al, 2017b ; Queiroga et al, 2021 ; Ait Djebbara et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…T. cruzi molecules such as surface glycoinositolphospholipids (GPIs) and parasite DNA/RNA sequences can be sensed by TLRs ( Macaluso et al, 2023 ). In fact, several investigators have shown the significance and involvement of TLRs in the control of T. cruzi infection ( Caetano et al, 2011 ; Castillo et al, 2017b ; Queiroga et al, 2021 ; Ait Djebbara et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lower levels of TLR2, TLR4, TLR9, TRIF and Myd88 transcripts was associated with the infection of mice with high virulent T. cruzi strains. Consequently, reduced IL-12 levels were observed in these mice and led to high parasitemia, myocarditis and mortality [ 66 ].…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…For example, seasonality, parasite strain, vector species, and vector nutrition play key roles in replication within the vector. In the vertebrate host, altitude, parasite genetic structure, and host immune response influence the parasite-host relationship [ 27 , 28 ].…”
Section: Life Cycle Of Trypanosoma Cruzimentioning
confidence: 99%